Sono meu, sonho meu... : velhice e sono - Fonseca, Bernadete Cristina Ferreira Fleury da (2011)
The change in the base of the population pyramid shows that the population is aging, deserving attention and importance in our society in many ways. Considering the aspect of health, aging increases the chances of the emergence of chronic and degenerative diseases, loss of functional and social roles, which may impact on the quality of life of these subjects. In this aspect of health, we emphasize the importance of sleep in older adult life, from a sample of elderly women who had changes in sleep patterns, intending with this study, we study the physiological aspect of sleep in his old age, diseases and disorders associated most commonly found in older people and the impact that sleep may cause the quality of life in this population. The study is based on a literature review, exploratory, descriptive and reflective, in which articles were selected from data source SciELO, PubMed, and Lilacs, who discussed the phenomenon of sleep in old age, from 1995 to 2011. Sleep in aging has its own peculiarities in this age group, with decrease in stages 3 and 4, representing one of the most frequent complaints among the elderly, worse quality when associated with clinical conditions such as Sleep Apnea, Obesity, Diabetes Mellitus, Anxiety and Depression , medication use, social conditions such as institutionalization, bereavement and widowhood. The poor quality of sleep adversely affects the quality of life for seniors, but we can not generalize that elderly people sleep badly, because active seniors healthy and have no complaints or sleep disorders. Therefore, it is necessary that professionals involved in care of the elderly, given the condition of sleep in old age